Mapping of deltaic aquifers with the combined application of DC and TEM soundings - Alexopoulos, J.D.; Dilalos, S.; Mitsika, G.S.; Poulos, S.E. (Near Surface Geoscience 2019- 25th European Meeting of Environmental and Engineering Geophysics, 2019)
<span style="color: #677078; font-family: Roboto, Verdana, Trebuchet, Helvetica, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The current study aims to clarify the hydrogeological regime of the deltaic valley of Pinios river (Thessaly, Greece). Its purpose is to map the existing aquifers below the deltaic plain, but also to assess the quality of their water (detect possible seawater intrusion), through the combined application of VES and TEM soundings. The results of the geophysical data processing revealed that the shallow (phreatic) aquifer is not detected throughout the entire deltaic plain, but only in the central and northern parts of the region, with thickness of 5–10 meters. Additionally, a deeper aquifer has been detected, with a maximum thickness equal to 100 meters. The interpretation of the geophysical soundings indicated that great part of the deeper aquifer has been affected by a saline intrusion that has also been noticed by hydrochemical data. Based on the fact that Pinios deltaic plain is a highly productive agricultural area, the irrigation system has to be reevaluated in order to constrain the extension of the seawater intrusion.